Regional development potential: the evolution of methodological approaches in the Russian Federation domestic regional studies - Natalia Zigern-Korn (European Regional Science Association (ERSA), 2012)
Regional development potential: the evolution of methodological approaches in the domestic regional studies The problems of methodology and method tools in the regional development potentials study are under consideration. Definition of the category "potential" is considered on the number of domestic (Russian) works and research example. The evolution of researchers methodological positions from the Soviet period to the present time are subjected to analysis. A step change in the content of the natural-resource potential while geosystem approach to natural resource research is gradually enriched with economic content is shown. We prove the incorrectness of identifying the category 'potential' with the category of 'resources', and estimate it in the context of underutilized resources to be used in the modern region development forecasts. The main areas of regional potentials investigation in recent studies are distinguished and discussed by author. They are: the study of individual potentials as factors of regional development and as a set of some functional significance resources; the search of regional development potential integral index as a set of resources and opportunities for regional development. It is noted that in the last few years, the notion of potential appears and develops in the context of regional development tasks and out of forecast and analysis of regional development, this category makes no sense. But, according to the author, the previous domestic attempts to create a logical system of views on the issue of socio-economic forecasting by regional development potential assessing both from a solely geosystem approach, and with the help of new research concepts for domestic regional economy (reproduction approach and new concepts of the region) have been failed. The article shows geosystem constructive approach to analyze the spatial dynamics of regional factors for development. Further to this the author concept of 'functional capacity of the territory' is introduced. To analyze the temporal (time) dynamics of economic systems the relevance of an evolutionary approach, studying the cyclical patterns of development of complex systems is proved. Due to the cyclical patterns of complex systems development this approach emphasis on the evolution of the regional policy goals and objectives according different stages of social development and in different technological structures.
Keywords: 330